Pharmacological characterisation of medicinal plants used ethnobotanically for the treatment of sexually transmitted infections - Sanyu, Keren Ruth (Rhodes University, 2026)
Sexually transmitted infections have become a major public health issue, affecting millions of people. These infections can cause serious consequences such as infertility in women, urethritis and prostatitis in men, chronic pain, or an increase in HIV transmission. Antimicrobial resistance is a major challenge in the treatment of diseases, including sexually transmitted infections (STIs). In recent years, research has focused on developing new potential therapeutic agents to prevent and treat infections using medicinal plants, which have been analysed for their bioactive compounds that possess therapeutic properties. This study primarily focuses on investigating the antimicrobial activity in vitro of Hypoxis hemerocallidea and Hydnora africana against common bacterial pathogens and the effect of liver drug metabolizing enzymes, as well as determining the antioxidant potential of the plants. The corms of H. hemerocallidea and H. africana were collected from a South African professional indigenous health practitioner, in the Eastern Cape, Makhanda (Grahamstown). Plant extraction was performed by maceration with the solvents: hexane, dichloromethane, methanol, and water. The resulting extracts were subjected to qualitative phytochemical analysis and a quantitative total phenolic content and total flavonoid content tests were conducted using gallic acid and quercetin as the standards. The antimicrobial activity of the plant extracts was assessed using a percentage viability antimicrobial assay against four bacterial strains: Acinetobacter baumannii, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The antioxidant activity was determined qualitatively and quantitatively using the DPPH radical scavenging assay, using ascorbic acid as the standard and absorbance measured at 517 nm. The liver enzyme inhibition potential of the plant extracts was evaluated using commercial recombinant cytochrome P450. The qualitative phytochemical screening of H. hemerocallidea and H. africana in different solvent extracts revealed the presence of phenols, flavonoids, tannins, and alkaloids, especially in the methanol and water extracts. The results of the total phenolic test for H. hemerocallidea and H. africana revealed that the plant extracts contain phenolic compounds, and the quantity of the phenolic compounds generally increased with increasing extract concentration. The same applied for the total flavonoid content in both plants, which showed a similar trend to the phenolic content, with the methanol extract having the most flavonoids. The results of the qualitative DPPH dot plot showed that the extracts of H. hemerocallidea and H. africana have compounds in them that possess some level of antioxidant activity. The quantitative DPPH radical scavenging assay demonstrated that the extracts had moderate antioxidant activity, compared to ascorbic acid. The methanol extract of both plants demonstrated the most significant radical scavenging activity showing a concentration-dependent increase. The plant extracts demonstrated different levels of antimicrobial activity, with the most notable antibacterial activity for H. hemerocallidea and H. africana being against Staphylococcus aureus. The results revealed that the extracts exhibited some CYP3A4 enzyme inhibitory activity, notably at high concentrations, with the methanol extract exhibiting inhibitory effect much higher than ketoconazole. The corms of H. hemerocallidea and H. africana contain different phytochemicals such as phenols, flavonoids, tannins, alkaloids that possess antioxidant and antibacterial properties, as well as some CYP3A4 enzyme inhibitory activity, notably at high concentrations. Further studies are needed to expand on the mechanism of action of these plant extracts and compounds.
Keywords: Uncatalogued